2022
DOI: 10.7150/ijbs.71134
|View full text |Cite
|
Sign up to set email alerts
|

Activation of VIPR1 suppresses hepatocellular carcinoma progression by regulating arginine and pyrimidine metabolism

Abstract: Background and aims: Vasoactive intestinal polypeptide type-I receptor (VIPR1) overexpression has been reported in numerous types of malignancies and utilized to develop novel target therapeutics and radiolabeled VIP analogue-based tumor imaging technology, but its role in liver carcinogenesis has not been explored. In the current study, we investigated the role of the VIP/VIPR1 signaling in controlling hepatocellular carcinoma (HCC) progression. Approach and results: By analyzing clinical samples, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…injection) for continuous 21 weeks, to induce HCC model as described previously 19. Mice were also subjected to single DEN injection or chronic CCl 4 alone 24…”
Section: Methodsmentioning
confidence: 99%
“…injection) for continuous 21 weeks, to induce HCC model as described previously 19. Mice were also subjected to single DEN injection or chronic CCl 4 alone 24…”
Section: Methodsmentioning
confidence: 99%
“…Regarding these genes, low expression of AC004538.3 , VIPR1 , and MASP2 was associated with a poor prognosis (Logrank p < 0.05; Figure 7 ). Furthermore, VIPR1 exhibited a strong association with the occurrence of HCC ( Table 4 ) ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 12 characteristic genes are primarily enriched in pathway associated with metabolic process. Among the characteristic gene generated from the model, loss of VIPR1 expression in HCC facilitated CAD phosphorylation and tumor progression, suggesting that the restoration of VIPR1 and treatment with the VIPR1 agonist may represent a promising approach for HCC treatment ( 32 , 36 ). Our research suggested that VIPR1 may play a role in the classification of early stage HCC and advanced HCC, but further research is needed to determine its specific function.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that VIP/VIPR1 signaling stimulates the transactivation of HER-2 and EGFR in human breast cancer and that VIPR1 expression is maintained in breast tumors and might have a potential role in carcinogenesis 10 . Recent reports suggest that VIP/VIPR1 signaling protects cancer stem cells from drug-induced apoptosis by dephosphorylating pro-apoptotic Bcl2 family member BAD 11 . This dual role of VIPR1 in breast cancer is noteworthy since its association with tumor suppression and tumorigenic signalings' activation.…”
Section: Discussionmentioning
confidence: 99%